When We Were Young : A Novel - Kingsbury, Karen (New York Howard Books, 2018)
"From #1 New York Times bestselling author Karen Kingsbury comes a classic story about second chances, featuring the beloved Baxter family and a young father who finds his whole world turned upside down on the eve of his divorce"--
Keywords: Social media -- Fiction; Marriage -- Fiction; FICTION / Christian / Romance; FICTION / Christian / General; Christian fiction; Domestic fiction